L2 SELF-CONFIDENCE: AN EXAMINATION OF INDONESIAN UNIVERSITY STUDENTS IN VARIOUS ENGLISH FOR SPECIFIC PURPOSES CLASSES - Dewi, Lusiana Puspita; Subekti, Adaninggar Septi (Sanata Dharma University, 2024)
The study aims to investigate second/foreign language (L2) confidence of English for Specific Purposes (ESP) learners. It employed a survey method. It involved 213 ESP learners from five different departments. Using descriptive statistics on SPSS, the study found a low-moderate level of L2 self-confidence among the participants. They reported interest in engaging in speaking activities in ESP classes. Nonetheless, they reported low L2 self-confidence regarding giving opinions and leading discussions in English and a low perception of their language competence in general. This low level of confidence could be attributed to the nature of ESP classes, which necessitate learners to study discipline-related vocabulary and language expressions, as well as several general aspects of L2 learning, such as pronunciation and grammar. Implications include encouraging ESP teachers to conduct more small-group-scale activities. That is to boost learners' confidence, increase learner-talk, and provide a safe environment for less confident learners to engage in the activities. This study contributes to the understanding of Indonesian ESP learners' self-confidence, and this could inform future studies involving ESP learners in Indonesia. Future quantitative studies on L2 confidence could use more representative samples. It is also strategic to conduct a mixed-methods study involving ESP teachers to allow triangulation.